Impact of excise tax on consumption, brand loyalty and health awareness: Evidence from the United Arab Emirates - Atia Hussain; Walaa Wahid Elkelish; Muhammad Al Mahameed (Cogent Business & Management)
The main purpose of this paper is to empirically analyze the impact of excise tax on excisable goods consumption, brand loyalty and health awareness in the United Arab Emirates (UAE) market. The research is conducted based on the self-administered questionnaire collected from the residents of the UAE. The snow-ball sampling technique is used to collect the data set during 2022. A total of 559 usable questionnaires were analyzed. This paper uses the multiple regression analysis model (OLS) to test the study hypothesis. The findings of the research show that implementation of excise tax has no significant impact on the consumption of excisable goods. The findings show a positive relation between implementation of excise tax and customers’ brand loyalty. Likewise, the excise tax implementation has a positive impact on the health awareness among the residents of the UAE for the consumption of excisable goods. The findings of this paper would provide insights to the policymakers for formulating the future excise tax policies and extending the scope of excise tax to the other unhealthy products in the emerging market (UAE). This paper provides evidence supporting the impact of implementation of excise tax on the consumption, brand loyalty and health awareness of the individual consumers in the emerging economy. To the best of the authors’ knowledge, this is the first study to research and test the consumption behavior of individuals through the collection of primary data set since the excise tax is implemented in the Gulf Cooperation Council specially in the UAE economy which includes the excisable products, i.e., tobacco, carbonated drinks, energy drinks, sweetened beverages and electronic smoking devices.